2011
DOI: 10.1159/000323933
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Factors for Chronic Pancreatitis and Pancreatic Cancer

Abstract: Chronic pancreatitis has long been thought to be mainly associated with immoderate alcohol consumption. The observation that only ∼10% of heavy drinkers develop chronic pancreatitis not only suggests that other environmental factors, such as tobacco smoke, are potent additional risk factors, but also that the genetic component of pancreatitis is more common than previously presumed. Either disease-causing or protective traits have been indentified for mutations in different trypsinogen genes, the gene for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 166 publications
0
25
1
2
Order By: Relevance
“…Smoking is the most important environmental risk factor for pancreatic cancer [18], while obesity has been associated with a higher incidence of pancreatic cancer in epidemiological studies [19]. The etiological role of alcohol in pancreatic cancer has been hard to ascertain because of the close association between alcohol and chronic pancreatitis, a known risk factor for pancreatic cancer [20].…”
Section: Risk Groups: How Do We Find Pancreatic Cancer Earlier?mentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking is the most important environmental risk factor for pancreatic cancer [18], while obesity has been associated with a higher incidence of pancreatic cancer in epidemiological studies [19]. The etiological role of alcohol in pancreatic cancer has been hard to ascertain because of the close association between alcohol and chronic pancreatitis, a known risk factor for pancreatic cancer [20].…”
Section: Risk Groups: How Do We Find Pancreatic Cancer Earlier?mentioning
confidence: 99%
“…At the microscopic level, ductal adenocarcinomas form more or less well defined duct structures, and are embedded in an extensive, fibrotic stroma ( Figure 4B). Immunohistochemically, pancreatic cancers may express CEA, CA 19-9, CA125, SMAD4, as well as cytokeratins (CK 5/6,7,8,18,and 19) and mucins (MUC1, MUC4, MUC5AC, and MUC6). Increasing tumor size and invasion correlate with poor patient survival [74].…”
Section: Pathological Evaluation: How Do We Improve Prognostic Accuracy?mentioning
confidence: 99%
“…Of these, cigarette smoking has been regarded as the most important risk factor. Smokers have 2-fold to 3-fold increased risk of PC compared to non-smokers with cigarette smoking accounting for approximately a quarter of PC incidence Silverman et al, 1994;Fuchs et al, 1996;Lowenfels et al, 2006;Ko et al, 2007;Bao et al, 2009;Talamini et al, 2010;Nitsche et al, 2011). Hereditary PC accounts for 5%-10% of all cases.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that genetic factors play key roles in PC pathogenesis (Lin et al, 2001;Lowenfels and Maisonneuve, 2003;Duell et al, 2008;Landi, 2009;Chu et al, 2010;Nitsche et al, 2011). It has also been suggested that the XRCC1 gene is one of the most important candidate genes influencing the susceptibility to PC (Duell et al, 2002;Li et al, 2006Li et al, , 2007McWilliams et al, 2008;Nakao et al, 2012), and its genetic polymorphisms are involved in modulating PC risk (Duell et al, 2002;Hung et al, 2005;Li et al, 2006;Mandal et al, 2010).…”
Section: Discussionmentioning
confidence: 99%